ROLE OF AEROBIC BACTERIA ON GANGRENE AMONG SAMPLE OF DIABETES MILLITUS IRAQI PATIENTS - Fouad E. Abdul Amjeed; D. S. AL-Rubaye (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to identify the types of aerobic bacteria in individuals with gangrene. Among 106 swabs from the site of gangrene in diabetic individuals, the percentage of females was 37 (34.99%), and a male was 69 (65.1%). The highest percentage at age group 46-55 year was in male (33.33%) and 24.32% in females, while the lowest percentage at 15-25 year in female was (5.41%) while in male was zero. The mean age was 54 years among males and females. Out of 106 swabs, 76 different types of bacteria were isolated. The Gram-positive bacteria were dominant 42 (55.3%), the most common pathogen was Staphylococcus aureus (57.1%), and the lowest was Micrococcus (4.9%). The Gram-negative bacteria was 34 (44.7%), with the highest percentage was Pseudomonas (52.9%) and the lowest percentage was Proteus (3%). Kirby-Bauer Disk Diffusion test for antibiotic sensitivity represented those Gram-negative bacteria had a high rate of resistance to vancomycin, clindamycin, and ceftazidime (94.12%) in the same proportion, while the lowest resistance was to Imipenem and Colistin (52.94%), (14.71%) respectively. Gram positive bacteria showed a high resistance to Ceftazidime (100%) and low resistance to Gentamicin and Imipenem (47.62%) then Colistin (30.95%).